LOCAL DRAMA SERIAL KHAI-A MULTILAYERED STORYLINE PORTRAYING REVENGE AS SOCIAL INTERACTION - Nomana Masood; Ahmad Bilal (Journal of Arts & Social Sciences, 2024)
The drama serial “Khaie” depicts multidimensional script revealing diverse characterization and brutal events in a cultural scenario. The aim of the research is to investigate the influence of the OTT platforms in the art of storytelling and in the portrayal of characters. This paper highlights the psychic condition of the female lead character as an avenger, a role unacceptable in local society. A comparative analysis is created between local drama serial “Khaie” and series “Game of the Thrones” demonstrating a comparable style of storytelling along with the cultural, social, and psychological aspects of revenge between the content of both serials. The outcome of the research suggests that the influence of the OTT content is not only changing the traditional style of storytelling, typical subject matters and portrayal of characters. It is also shifting the mindset of the audiences in accepting the strength, power image and diverse roles of women.